2005
DOI: 10.1016/j.nuclphysa.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment coefficient and effective mass for conduction neutrons in neutron star crust: simple microscopic models

Abstract: Abstract. In the inner crust of a neutron star, at densities above the "drip" threshold, unbound "conduction" neutrons can move freely past through the ionic lattice formed by the nuclei. The relative current density n i = nv i of such conduction neutrons will be related to the corresponding mean particle momentum p i by a proportionality relation of the form n i = Kp i in terms of a physically well defined mobility coefficient K whose value in this context has not been calculated before. Using methods from or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(141 citation statements)
references
References 24 publications
3
136
1
Order By: Relevance
“…in which the interaction termĤ int will be absent in the independent particle limit corresponding to the kind of model used [6] in our preceding first quantised treatment.…”
Section: Hamiltonian For the Independent Particle Limitmentioning
confidence: 99%
See 2 more Smart Citations
“…in which the interaction termĤ int will be absent in the independent particle limit corresponding to the kind of model used [6] in our preceding first quantised treatment.…”
Section: Hamiltonian For the Independent Particle Limitmentioning
confidence: 99%
“…Since (particularly for the middle layers of a neutron star crust, where the effective mass enhancement is likely [6,7] to be most important) we are still far from having a sufficient knowledge of the solutions ϕ kα {r} for the independent particle model, it will evidently take some time before we can hope to obtain a complete evaluation of the solutions for the coupled equations for ϕ 0 kα {r} and ϕ 1 kα {r} using an accurate estimate of the coupling coefficient ∆{r} . In the meanwhile, as an immediately available approximation, offering the best that can be hoped for as a provisional estimate in the short run, we can use an ansatz of the standard BCS kind, which means adopting the prescription U kα,lβ = cos θ kα δ kl δ αβ , V kα,lβ = sin θ kα δ −k,l δ αβ .…”
Section: Bogoliubov Treatment Of Pairingmentioning
confidence: 99%
See 1 more Smart Citation
“…[5]). Despite the absence of viscous drag, the neutron superfluid can still be coupled to the crust due to non-dissipative entrainment effects arising from elastic Bragg scattering of dripped neutrons by the crystal lattice [6,7]. Recent calculations have shown that in some regions of the inner crust only a very small fraction of dripped neutrons participate in the superfluid dynamics [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a preceeding work [1,2] we have introduced a macroscopic effective mass m ⋆ relevant for hydrodynamical simulations, such that the momentum of the neutron superfluid is given by the mean neutron velocity times this effective mass in the crust rest frame. In a (super)fluid mixture, in general the momentum of one species is a linear combination of the particle currents of the other components.…”
Section: Introductionmentioning
confidence: 99%